When giving is good for encouraging social entrepreneurship. Issue 4 (November 2020) - Le, Truc Thanh; Nguyen, Thi Nguyet Que; Tran, Quan Ha Minh
Highlights: Cognitive empathy relates positively to prosocial behavior. Emotional empathy relates positively to prosocial behavior. Prosocial behavior relates positively to social entrepreneurial intention. Prosocial behavior mediates the effect of cognitive empathy on social entrepreneurial intention. Prosocial behavior mediates the effect of emotional empathy on social entrepreneurial intention. Opportunity evaluation moderates the effect of prosocial behavior on social entrepreneurial intention. Opportunity exploitation moderates the effect of prosocial behavior on social entrepreneurial intention. Abstract: We develop a cognitive-affect model of social entrepreneurship that begins with empathy (i.e. perspective taking and empathic concern) and progresses through prosocial behavior to social entrepreneurship intention. We further propose two contingencies – namely entrepreneurial opportunity evaluation and exploitation - that moderate the proposed relationships. We verify theses effects with a sample of 537 respondents. Results suggest that prosocial behavior mediates the relationship between empathy (perspective taking and empathic concern) and social entrepreneurial intention. We also find that opportunity evaluation and opportunity exploitation moderate this mediating pathway. Chinese Abstract: 我们发展了一个社会企业家的认知—影响模型, 它从共情开始 (即接受观点和共情关注), 并通过亲社会行为发展到社会企业家意向. 我们进一步提出了两个偶发事件—创业机会评估和利用—来调节所提出的关系. 我们以 537 名受访者为样本验证了这些效应. 结果表明, 亲社会行为在共情 (接受观点和共情关注) 和社会创业意向之间起到中介作用. 我们还发现机会评估和机会利用调节了这一中介路径.